Empowering Deaf Children Through KatakLarita in Sexual Safety Education - Ni Luh Putu Yunianti Suntari Cakera; I Ketut Labir; Ni Putu Dessy Parmitha Sari; Ni Made Tariani; Dewa Gede Nata Raditya (Indian Journal of Public Health)
In the depth topic of child protection, the alarming prevalence of sexual violence remains a dark thread that permeates every layer of society. This report delves into the implementation of “KatakLarita,” an innovative and inclusive educational initiative aimed at enhancing sexual safety education for deaf children. Results showed that using “KatakLarita” as learning media helped deaf students improve significantly in sexual safety knowledge.